Phloridzin Reveals New Treatment Strategies for Liver Fibrosis - Yahong Shi; Tun Yan; Xi Lu; Kai Li; Yifeng Nie; Chuqiao Jiao; Huizhen Sun; Tingting Li; Xiang Li; Dong Han (MDPI AG, 2022)
Liver fibrosis is an urgent public health problem which is difficult to resolve. However, various drugs for the treatment of liver fibrosis in clinical practice have their own problems during use. In this study, we used phloridzin to treat hepatic fibrosis in the CCl4-induced C57/BL6N mouse model, which was extracted from lychee core, a traditional Chinese medicine. The therapeutic effect was evaluated by biochemical index detections and ultrasound detection. Furthermore, in order to determine the mechanism of phloridzin in the treatment of liver fibrosis, we performed high-throughput sequencing of mRNA and lncRNA in different groups of liver tissues. The results showed that compared with the model group, the phloridzin-treated groups revealed a significant decrease in collagen deposition and decreased levels of serum alanine aminotransferase, aspartate aminotransferase, laminin, and hyaluronic acid. GO and KEGG pathway enrichment analysis of the differential mRNAs was performed and revealed that phloridzin mainly affects cell ferroptosis. Gene co-expression analysis showed that the target genes of lncRNA were obvious in cell components such as focal adhesions, intercellular adhesion, and cell-substrate junctions and in metabolic pathways such as carbon metabolism. These results showed that phloridizin can effectively treat liver fibrosis, and the mechanism may involve ferroptosis, carbon metabolism, and related changes in biomechanics.